Association of variants in FABP4, FASN, SCD, SREBP1 and TCAP genes with intramuscular fat, carcass traits and body size in Chinese Qinchuan cattle. (October 2022) - Gao, Y.Y.; Cheng, G.; Cheng, Z.X.; Bao, C.; Yamada, T.; Cao, G.F.; Bao, S.Q.; Schreurs, N.M.; Zan, L.S.; Tong, B.
Abstract: This study aimed to genotype the variants in FABP4, FASN, SCD, SREBP1 and TCAP genes, and to analyze their associations with intramuscular fat (IMF) content, carcass traits and body size in Chinese Qinchuan cattle (QC). The association studies showed that the FABP4 c.220A > G polymorphism was significantly associated with ultrasound longissimus muscle depth (ULMD) and IMF, the FASN g.16024A > G polymorphism was significantly associated with ULMD and some body size traits, the SREBP1 84 bp indel was significantly associated with back fat thickness, ULMD and some body size traits. The frequencies of well-characterized A allele in FABP4 c.220A > G in Korean cattle (KOR) and Japanese Black cattle (JB), T allele in SCD g.8586C > T in KOR, SS genotype in SREBP1 84 bp indel in KOR and JB, DELDEL genotype in TCAP g.592-597CTGCAGinsdel in KOR were significantly higher than in Chinese cattle breeds. Thus, the associated four polymorphisms were expected to be genetic selection markers for meat quality, carcass traits and body size of QC.